A Design-Based Instructional Module Integrating Motivation and Self-Regulated Learning in EFL Learning Contexts - IGA Widari; Iwan Jazadi (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This study addresses the persistent challenge of low and unstable motivation and underdeveloped learning strategies among first-year EFL students in regional Indonesian higher education contexts, where limited academic support and low-resource conditions often hinder the development of learner autonomy. In response, it aimed to develop and validate a Motivation and Learning Strategies Module (MLSM) integrating Self-Determination Theory (SDT), the ARCS motivational model, and Self-Regulated Learning (SRL) principles. A Research and Development (R&D) design adapted from Borg and Gall and Dick and Carey models was employed, combined with a mixed-methods pre–post evaluation approach. The participants were 24 first-year EFL students, along with three expert validators and six students for qualitative feedback. Data were collected through motivation and learning strategy questionnaires, validation rubrics, reflective interviews, and open-ended responses. Quantitative data were analyzed using descriptive statistics and paired-samples t-tests, while qualitative data were analyzed using thematic analysis. The findings showed no statistically significant difference between pre-test and post-test scores of motivation and learning strategies (p > .05), indicating no significant short-term improvement. However, qualitative results revealed increased learner awareness of motivation, improved self-management, greater engagement, and emerging self-regulated learning behaviors. Expert and student evaluations further indicated that the module was highly feasible, relevant, and contextually appropriate for EFL instruction in low-resource settings. The study develops a context-sensitive instructional module integrating SDT, ARCS, and SRL into a unified framework for EFL learning. It suggests that while the MLSM does not produce immediate measurable gains in motivation, it facilitates reflective learning processes and supports the development of learner autonomy. Practically, the module offers an adaptable instructional resource for EFL educators in low-resource higher education contexts seeking to strengthen motivational and strategic learning support.